THE RELATIONSHIP OF INTERPERSONAL COMMUNICATION KNOWLEDGE LEVEL WITH THE APPLICATION OF THERAPEUTIC COMMUNICATION IN NURSING STUDENTS AT STIKES MEDISTRA INDONESIA IN 2022 - Ramadhani, Nur Fajriah; Kiki Deniati; Arabta Malem Peraten Pelawi (Jurnal Medicare, 2022)
Interpersonal communication is communication between two or more people and becomes the basis of therapeutic communication. Therapeutic communication is a process of delivering messages by nurses to patients that influence each other and aim to provide a patient healing process. The application of therapeutic communication based on knowledge will be permanent and even become a habit so that the application of therapeutic communication is not difficult to do. With the application of good therapeutic communication, the nursing process can run optimally. The purpose of the study was to determine the relationship between the level of knowledge of interpersonal communication and the application of therapeutic communication to nursing students at STIKes Medistra Indonesia in 2022. The analytical quantitative research method with a Cross-Sectional approach, and sampling technique using stratified random sampling totaled 163 students. The conclusion is that there is a relationship between the level of knowledge of interpersonal communication and the application of therapeutic communication to nursing students at STIKes Medistra Indonesia in 2022.